Relational Marketing Management in Islamic Educational Institutions in Enhancing Public Trust - Fakih Firdaus, Arif; Zohriah, Anis; Muin, Abdul; Muawanah, Uyu; Fitriani, Dini (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2026)
Relational marketing has become an important approach in the management of educational services, particularly in building long-term relationships and increasing public trust. However, previous studies tend to examine relational marketing and Islamic educational values separately, with limited integration between the two perspectives.  This study aims to analyze the role of relational marketing management in Islamic educational institutions in enhancing public trust. This research employs a qualitative approach using a systematic literature review method by reviewing relevant scientific sources published between 2020 and 2025. The findings indicate that relational marketing significantly contributes to increasing public trust through service quality, effective communication, stakeholder engagement, and the utilization of digital technology. In the context of Islamic education, relational marketing aligns with the principles of amanah (trustworthiness), ihsan (excellence), and ukhuwah (brotherhood), which strengthen ethical and sustainable relationships.  This study concludes that relational marketing is not only a marketing strategy but also a value-based managerial approach that supports the sustainability of Islamic educational institutions. Furthermore, this study contributes by integrating relational marketing concepts with Islamic values in enhancing public trust.